Study of PCL / MWCNT as an electrical scaffold - Chong, Xue Er (2015)
In this project, the optimal common solvents used for the solvent casting of Polycaprolactone(PCL), functionalized and non – functionalized multi – walled carbon nanotubes (MWCNTs) was being investigated. Based on the dispersion quality of the solutions, DMF and chloroform was selected for the solvent casting fabrication technique of the films containing different percentages of non – functionalized MWCNTs and PCL and another set of films containing different percentages functionalized MWCNTs and PCL. After fabricating the polymer composite films via the solvent casting technique, characterization tests to determine properties like dispersion quality, hydrophobicity, strength, conductivity and cell viability etc. were being carried out on the films.Following the characterization resultspatterning of the various films (i.e. 10% PCL, 15% PCL and films containing 5% of functionalized MWCNTs and 10% of PCL) were also carried out to determine the optimum feed rate of printing and the possibility of whether the solutions could be printed according to the shapes designed via BioCAD software. The results showed that solvent casting of the films was a simple process that enabled the production of porous films. The characterization test further proved that the films produce could aid in tissue engineering applications due to the properties they have. In addition, the optimum feed rate of printing was determined and the patterning of the films were also successful.